Leaching of a gold bearing partially roasted sulphide: laboratory scale studies - M. F. Almeida (2001)
This research aimed at defining a route for recovering precious metals from a very heterogeneousgold bearing sulphide and arsenide concentrate that was partially roasted and dumped by the 1960swhen Santo António mine closed. Gold occurs in this concentrate as free particles in the range of10-100 µm, most of them still enclosed in the pyrite and arsenopyrite matrix. Its content varies from20 to 150 g of Au/ton, being higher at the dump upper levels and in the finer concentrate fractions.Preliminary tests demonstrated the refractoriness of this product, since the leaching withconventional cyanide solutions and with other leaching solutions gave very low recoveries. However,high concentrated cyanide solutions recover more than 60% of Au, although with high NaCNand lime consumptions and poor settling characteristics. Iron was shown to be highly dissolved inthese solutions.Some prior treatments clearly favoured the cyanidation process, in particular a roasting step.Thus, a large number of roasting experiments was carried out to define the most favourableconditions for recovering gold. However, no clear relationship between roasting conditions and golddissolution was found due to the heterogeneity of the product and high variance of gold experimentalrecoveries. These recoveries were calculated considering gold contained in both the leachingresidues and leachates, and uncertainties of these results are relatively high.Roasting the product at 450-700 °C for 1 h guarantees a high probability to dissolve at least 74%Au in a highly concentrated NaCN solution stirred for 24 h. The 600-700 °C roasting range is clearlypreferable for consuming less cyanide and lime. Pre-washing the roasted product seems not to reducethe cyanide consumption.Regarding the silver recovery, the NaCN and lime consumption are higher while using theproducts roasted at the lowest tested temperatures. Products roasted at higher temperatures havebetter settling performance.